Redistribution of Grain Boundary Misorientation and Residual Stresses of Thermomechanically Simulated Welding in an Intercritically Reheated Coarse Grained Heat Affected Zone - Giancarlo Sanchez Chavez (MDPI AG, 2021)
A study of the migration of the grain boundary misorientation and its relationship with the residual stresses through time immediately after the completion of a thermomechanical simulation has been carried out. After physically simulating an intercritically overheated welding heat affected zone, the variation of the misorientation of grain contours was observed with the electron backscatter diffraction (EBSD) technique and likewise the variation of the residual stresses of welding with RAYSTRESS equipment. It was observed that the misorientation of the grain contours in an ASTM DH36 steel was modified after the thermomechanical simulation, which corresponds to the measured residual stress variation along the first week of monitoring, with compressive residual stresses ranging from 195 MPa to 160 MPa. The changes in misorientation indicate that the stress relaxation phenomenon is associated with the evolution of the misorientation in the microstructure caused by the welding procedure. On the first day, there was a fraction of 4% of the kernel average misorientation (KAM) values at 1° misorientation and on the fourth day, there was a fraction of 7% of the KAM values at 1° misorientation.